«The elements of «theatricality» іn the novel «Crazy» by Nechuy-Levitsky - Муравецька, Ярослава Сергіївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The article deals with the phenomenon of impact of theatre on 19th century culture by the example of the novel «Crazy» by Nechuy-Levitsky. The attention is concentrated on the distinction between the concepts of «theatricality» and «dramatic» and determination the boundaries of these terms. It ware analized the existing theatrical elements in the text, and noted the concepts of «disguise» and «duality» of the protagonist. The «theatrality» was studied as one of the elements of plot.